On the intricate relation between theory and description: A linguist’s look at The Cambridge Grammar of the English Language - Mendikoetxea, Amaya (Círculo de Lingüística Aplicada a la Comunicación, 2023)
On the intricate relation between theory and description: A linguist’s look at The Cambridge Grammar of the English Language.